2017
DOI: 10.1159/000481347
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Persistence of Risky Drinking in Adults: An 11-Year Follow-Up Study

Abstract: Aim: To examine the long-term predictors of persistence of risky drinking in a baseline group of risky drinkers in whom alcohol use disorder had not been diagnosed. Methods: The data was derived from a representative sample of the Finnish adult population aged 30 years or more, surveyed at 2 time points in the years 2000 (n = 5,726) and 2011 (n = 3,848, 67.2% of the baseline sample). Risky drinking was defined using BSQF-measurement (for men, 21 standard UK drinks or more per week; for women 14+ drinks) and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Given alcohol use is a necessary cause of alcohol attributable mortality (i.e. the event cannot occur in the absence of alcohol use), the observed mediated effect of smoking on alcohol-attributable mortality could be due to unmeasured harmful drinking, as alcohol use and smoking strongly correlate, or to combined effects that were not captured by the interaction between alcohol and smoking [60].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Given alcohol use is a necessary cause of alcohol attributable mortality (i.e. the event cannot occur in the absence of alcohol use), the observed mediated effect of smoking on alcohol-attributable mortality could be due to unmeasured harmful drinking, as alcohol use and smoking strongly correlate, or to combined effects that were not captured by the interaction between alcohol and smoking [60].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…The authors found that having a higher education, being male, and smoking at baseline significantly predicted risky drinking at follow-up, but baseline physical activity did not significantly predict or protect against risky drinking. [56] Ejsing et al (2015) analyzed data from 18,359 participants who were followed for an average of 21 years. Results indicated that the risk of developing an alcohol use disorder was significantly greater among participants who reported no leisure-time physical activity (HR = 1.45 [95% CI: 1.01–2.09]) for women; HR = 1.64 [95% CI: 1.29–2.1] for men) compared with moderate-to-highly active men and women after adjusting for potential confounders including smoking and baseline alcohol intake.…”
Section: Adults (Approximately 35–54 Years Old)mentioning
confidence: 99%
“…These risk factors are also associated with mental health problems (2)(3)(4)(5). Additionally, an association between harmful drinking and physical inactivity has been found (6)(7)(8). Drinking above the recommended limits increases the risk of developing health problems such as liver disease, hypertension, stroke, heart disease, and several cancers (9,10).…”
Section: Introductionmentioning
confidence: 99%